Everything Old is New Again: The Age of Consumer‐Centric Supply Chain Management. Issue 4 (10th January 2021) - Esper, Terry L.; Castillo, Vincent E.; Ren, Kate; Sodero, Anníbal; Wan, Xiang; Croxton, Keely L.; Knemeyer, A. Michael; DeNunzio, Steven; Zinn, Walter; Goldsby, Thomas J.
Abstract : Over the past several decades, the disciplines of marketing and logistics grew apart from their common historical origins as marketing became more behavioral and more quantitative, while logistics leaned toward a more operational orientation. We argue in this editorial that social and technological changes in the past 20 years, coupled with the effects of the COVID pandemic, have created the conditions for the two disciplines to reconnect. We propose that scholars and practitioners consider a consumer‐centric approach to supply chain management. Such an approach advocates that the entire supply chain should focus on consumer experience rather than mere customer service and that experiences might include issues such as last‐mile delivery, supply chain visibility, and consumer values. We also introduce the papers appearing in this issue of the journal.